Sustainable clean water production using bamboo activated carbon for rural residents in the Borneo Island - Kuok, King Kuok; Md. Rezaur, Rahman; Muhamad Khusairy, Bakri; Po Chan, Chiu; Mei Yun, Chin; Abdullah S, Al-Bogami; Khalid A., Alamry; Mohammed M., Rahman (BioResources, 2022)
In Sarawak, a state of Malaysia on Borneo Island, clean water supply coverage is estimated to be 81.4% in 2020, whereby those without access to clean water are rural residents. Although the state aims to achieve full clean water supply coverage by 2025, budget limitations make this impossible. This research proposes a decentralized water supply system that harvests rainwater and river water to supply rural households with clean water. The selected study area is Pelaman Monggak, a rural village in Bau District, Sarawak. The rainwater storage tank was modelled using the Tangki NAHRIM (NAHRIM Tank). The results showed that for a rural household of five people, the reliability for a tank size of 2 m3 is 84.5%. From 2010 to 2019, the rainwater storage tank can supply rainwater for 3044 days, with the remaining 608 days supplied by river water. As river water is not safe for potable use, treatment is needed. The proposed water treatment process for river water includes bamboo activated carbon adsorption, membrane microfiltration, and UV disinfection to improve the river water quality from Class II to Class I. For rainwater, two treatment processes, namely membrane microfiltration and UV disinfection, are sufficient to produce safe drinking water quality